Psychometric study of the European Portuguese version of the PedsQL 3.0 Cancer Module - Santos, Susana (2016)
Background: Health-related quality of life (HRQoL) is an important outcome to assess the impact of cancer. This article examines the psychometric properties of the European Portuguese self-report version of the Pediatric Quality of Life InventoryTM Cancer Module (PedsQLTM 3.0 Cancer Module) in children and adolescents with cancer. Methods: The participants, 332 children/adolescents diagnosed with cancer (8–18 years old), completed measures to assess HRQoL (PedsQLTM 3.0 Cancer Module and DISABKIDS Chronic Generic Measure; DCGM-12) and anxiety (Revised Children’s Manifest Anxiety Scale - second edition; RCMAS-2). A subsample (n = 52) completed the PedsQLTM 3.0 Cancer Module a second time following one-week. The pediatric oncologists completed the Intensity of Treatment Rating Scale 3.0 (ITR 3.0). Results: For the whole sample, the PedsQLTM 3.0 Cancer Module demonstrated good item discrimination (rs = .30 to .54). The confirmatory factor analysis testing the presence of eight first-order factors loading significantly in a second-order factor revealed an acceptable fit (CFI = .91; RMSEA = .05). The correlation of PedsQLTM 3.0 Cancer Module with DCGM-12 (rs = .17 to .58), and with RCMAS-2 (rs = −.16 to–.51) attested convergent validity. This inventory demonstrated minimally acceptable to very good internal consistency (αs = .65 to .87) and temporal stability (ICCs = .61 to .81). Conclusions: These findings demonstrate that the European Portuguese self-report version of the PedsQLTM 3.0 Cancer Module is a valid and reliable instrument for assessing HRQoL in pediatric cancer. Keywords: European Portuguese version, PedsQLTM 3.0 Cancer Module, Health-related quality of life, Pediatric cancer, Psychometric properties